Huaier Induces Cancer Recovery by Rescuing Impaired Function of Transcription Control Based On the Individual Genomic Potential - Tanaka, Manami; Tanaka, Tomoo; Teng, Fei; Lin, Hong; Li, Ning; Luo, Zhu; Wei, Ding; Lu, Zhengxin (Archives of Clinical and Biomedical Research, 2020)
Background: Clinical significance of anti-cancer effects of Huaier has been emphasized recently. We have proved that a broad spectrum of Huaier effects was based on the rescue of the disrupted Hippo signalling pathway in Drosophila mutants, especially through the rescue of transcriptional dysregulation. Objective: We initiated clinical research for thorough understanding of molecular basis of Huaier effects. Methods: The obtained peripheral blood samples were analyzed by total RNA and non-coding small RNA sequencing on BGISEQ-500 Platform. Results: In the present study, we sequenced 92 samples sequencing from 31 patients, average generating over 7.4 Giga bases per sample. The results showed significant changes in transcriptional factors and corresponding genes, which resulted in quantitative and qualitative alterations of signaling networks responsible for rescuing all the molecular biological function, cellular component and biological processes. Those changes were identified through genome wide range, and that from RNA editing events, to the resulting transcriptomes with discovery of 24,344 novel transcripts. Drastic variance of up/down regulated genes were associated with siRNA- and miRNA-mediated post-transcription control. Transcriptional factor changes, mean 1,115 per person, integrated those altered transcripts and their functional networks for the rescue of damaged or disrupted control. We provided functional lineage map of these results to show the process of cancer recovery by the time course of Huaier administration. Conclusion: The present study identified that the cancer recovery by Huaier therapy was based on the rescue of transcription control not only in cancer lesion, but also in almost all biological systems. These changes depended on individual capability and flexibility of g